2012
DOI: 10.1007/s11368-011-0464-y
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 photocatalytic degradation of 4-chlorobiphenyl as affected by solvents and surfactants

Abstract: Purpose TiO 2 photocatalytic degradation of 4-chlorobiphenyl (PCB3) in aqueous solution under UV irradiation was investigated as affected by different environmental factors, including initial PCB3 concentration, TiO 2 content, UV intensity, H 2 O 2 concentration, cosolvents, and surfactants. Materials and methods The solution of PCB3 with TiO 2 was irradiated by medium mercury lamp. The concentration of PCB3 and intermediates was analyzed by GC-μECD and GC-MS. The values of point charge and bond length were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…From the above‐discussed hypotheses and optimization, it is clear that high surface area and porous SiO 2 adsorption site could contribute to the pollutant removal efficiency of the TiO 2 ‐SiO 2 aerogel if the composite is accessible by pollutant solution, which was confirmed by our previous study . As for non‐heat‐treated hydrophobic TiO 2 ‐SiO 2 aerogels, their photocatalytic ability was confirmed (Figure S1, SI), in order to improve their adsorption ability to pollutant solution, a lipophilic co‐solvent could be applied to modify the interface between TiO 2 ‐SiO 2 aerogel and solvent . In this study, the solvent water in methyl orange solution was replaced by ethanol in 1–50 vol.%, and the pollutant removal experiment was examined on the optimized TiO 2 ‐SiO 2 sample ( C si =6.5/ R =5:1) but without calcination.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…From the above‐discussed hypotheses and optimization, it is clear that high surface area and porous SiO 2 adsorption site could contribute to the pollutant removal efficiency of the TiO 2 ‐SiO 2 aerogel if the composite is accessible by pollutant solution, which was confirmed by our previous study . As for non‐heat‐treated hydrophobic TiO 2 ‐SiO 2 aerogels, their photocatalytic ability was confirmed (Figure S1, SI), in order to improve their adsorption ability to pollutant solution, a lipophilic co‐solvent could be applied to modify the interface between TiO 2 ‐SiO 2 aerogel and solvent . In this study, the solvent water in methyl orange solution was replaced by ethanol in 1–50 vol.%, and the pollutant removal experiment was examined on the optimized TiO 2 ‐SiO 2 sample ( C si =6.5/ R =5:1) but without calcination.…”
Section: Resultssupporting
confidence: 55%
“…[10] As for non-heat-treated hydrophobic TiO 2 -SiO 2 aerogels, their photo- catalytic ability was confirmed ( Figure S1, SI), in order to improve their adsorption ability to pollutant solution, a lipophilic co-solvent could be applied to modify the interface between TiO 2 -SiO 2 aerogel and solvent. [13] In this study, the solvent water in methyl orange solution was replaced by ethanol in 1-50 vol.%, and the pollutant removal experiment was examined on the optimized TiO 2 -SiO 2 sample (C si = 6.5/R = 5:1) but without calcination. The photolysis of methyl orange concentration, with 1 vol.% ethanol replacement, as a function of time presents a degradation of 40% of initial methyl orange concentration after 60 mins UV exposure, and the sample accomplished the degradation up to 99% of initial methyl orange concentration in 30 mins when 50 vol.% water was replaced by ethanol, shown in Figure 5.…”
Section: Photocatalytic Performance Of the Tio 2 -Sio 2 Aerogels Withmentioning
confidence: 99%
“…For example, PCBs were completely photodegraded in acetone and acetonitrile solutions, but hardly degraded in tetrahydrofuran, dimethylformamide, dimethyl sulfoxide, methanol, ethanol, propanol, and isopropanol solutions, due to the consumption of ROS (e.g., hydroxyl radical (cOH)) by these solvents. 28,42 It should be emphasized that these organic solvents not only inuence the degradation efficiency of PCBs, but also change the photodegradation pathway of PCBs, which resulted in different proles of PCB metabolites. For example, the hydroxylated chlorobiphenyl (OH-PCB) was the dominant intermediate of PCBs photodegradation via the hydroxylation reaction between cOH and PCBs in a TiO 2 /UV system in the presence of acetone.…”
Section: Overview Of Remediation Technologies For Pcbs Contaminated S...mentioning
confidence: 99%
“…Specifically, Wang et al 35 studied the photocatalytic degradation of 2chlorobiphenyl using TiO 2 and found that TiO 2 enhanced the catalytic degradation of 2-chlorobiphenyl with a rate constant of 0.029 min −1 . Zhu et al 36 also explored the use of TiO 2 in the photocatalytic degradation of 4-chlorobiphenyl and found that TiO 2 was capable of degrading 4-chlorobiphenyl with a rate constant of 0.009 min −1 . Paĺmai et al 37 reported that m-BiVO 4 /BiOBr and m-BiVO 4 /BiOBr/Pd were able to degrade 4-chlorobiphenyl with rate constants of 0.014 and 0.03 min −1 , respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%